Pengaruh Corporate Social Responsibility Terhadap Agresivitas Pajak dengan Insentif Pajak Sebagai Pemoderasi. (Studi pada perusahaan pertambangan di Indonesia) - Warsono Warsono; Yuli Ardianto (Forum Manajemen Indonesia (FMI), 2015)
This study aims toexamine the effectofcorporatesocialresponsibility(CSR) to taxaggresiveness with the tax incentive as a moderator. The study population used is the mining companies listed in Indonesia Stock Exchange. Sampling method using purposive samplingobtained by 34 companies of reach with 2011-2015. This study used Corporate Social Responsibility (as independend variable) and Tax Aggressiveness(as dependend variable) and Tax Incentive (as moderating vatriable). Tocontrol the effect of CSR to tax aggresiveness,primarily as a result of the use of moderating variable,this study used variable controls :Leverage, Size, Return on Assets (ROA), Capital Intensity and Inventory Intensity. The dependent variable in this study is tax aggressiveness. It was measured by usingproxy :effective tax rate(ETR).CSR has been carried out by using Corporate Social Responsibility Index (CSRI).Data analysis technique has been done by using Moderated Regression Analysis (MRA). The data was processed using SPSS 22. The result shows that CSR has negative influence to tax agressiveness. The higherthelevelof CSR disclosure of acorporation, thelower isthelevelof tax aggressiveness.Tax incentives is proven and capable to strenghthen the relations between CSR and Tax Aggressivenes. CSR stimultantly tested with the control variables showed similar result that it has negative influence the higherthe levelof CSR disclosure of acorporation, thelower isthelevelof tax aggressiveness. Keywords: Corporate Social Responsibility, Tax Aggressiveness, Efective Tax Rate